1999
DOI: 10.1161/01.atv.19.10.2364
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Exacerbates Early Atherosclerosis in Mice

Abstract: Abstract-Acute-phase proteins, which respond to systemic proinflammatory cytokines such as interleuken-6, are elevated in cardiovascular disease and are predictive markers of future ischemic events, even over decades. This suggests a role for proinflammatory cytokines and/or acute phase proteins in early lesion development. To explore this issue, we fed C57Bl/6 and nonobese diabetic male mice high-fat (20% total fat, 1.5% cholesterol) diets and ApoE-deficient male mice both high-fat and normal chow diets for 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
284
1
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 490 publications
(308 citation statements)
references
References 24 publications
11
284
1
6
Order By: Relevance
“…Both clinical observations and studies in transgenic mice have shown a link between IL-6 overexpression and several pathologic conditions, including atherosclerosis [53][54][55], Alzheimer's disease [56][57][58][59], and rheumatoid arthritis [60][61][62]. It is worth mentioning that statins, which have become important in the treatment of patients with coronary artery disease [63,64] and also have been reported to have beneficial effects in POAG [65], are associated with a reduction in serum levels of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Both clinical observations and studies in transgenic mice have shown a link between IL-6 overexpression and several pathologic conditions, including atherosclerosis [53][54][55], Alzheimer's disease [56][57][58][59], and rheumatoid arthritis [60][61][62]. It is worth mentioning that statins, which have become important in the treatment of patients with coronary artery disease [63,64] and also have been reported to have beneficial effects in POAG [65], are associated with a reduction in serum levels of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…65 In experimental atherosclerosis, the administration of recombinant IL-6 was found to accelerate atherogenesis in Apoe -/-mice. 66 However, not all animal studies show such activity of IL-6 in the development of atherosclerosis (reviewed by Kleemann et al 52 ). This could be related to its pleiotropic nature, having pro-and antiinflammatory effects.…”
Section: Targeting Chief Proinflammatory Cytokinesmentioning
confidence: 99%
“…1 To explore whether inflammation was an integral part of fatty lesion development in the murine model system, we recently studied the effect of weekly interleukin-6 (IL-6) injections on C57Bl/6 and C57Bl/6 apoE ko mice and observed 2-to 5-fold increased lesion size. 2 The greater effect was observed in the wild-type C57Bl/6 strain, suggesting that the very high cholesterol levels observed in apoE ko mice (Ͼ1000 mg/dL) may at least partly mask an underlying inflammation-related mechanism.…”
mentioning
confidence: 99%